Vascular reconstruction related to the extracranial vertebral artery: the presentation of the concept and the basis for the establishment of the bypass system - Wang, Xuan; Tong, Xiaoguang (Frontiers in Neurology, 2023)
The intracranial vertebrobasilar artery system has a unique hemodynamic pattern (vessel trunk converged bilateral flow with three groups of perforators directly arising from it), is embedded within intense osseous constraints, and is located far from conventional donor vessels. Two major traditional modalities of posterior circulation revascularization encompass the superficial temporal artery to the superior cerebellar artery and the occipital artery to the posteroinferior cerebellar artery anastomosis, which are extracranial-intracranial low-flow bypass with donor arteries belonging to the anterior circulation and mainly supply focal perforators and distal vascular territories. As our understanding of flow hemodynamics has improved, the extracranial vertebral artery-related bypass has further evolved to improve the cerebral revascularization system. In this article, we propose the concept of “vascular reconstruction related to the extracranial vertebral artery” and review the design philosophy of the available innovative modalities in the respective segments. V1 transposition overcomes the issue of high rates of in-stent restenosis and provides a durable complementary alternative to endovascular treatment. V2 bypass serves as an extracranial communication pathway between the anterior and posterior circulation, providing the advantages of high-flow, short interposition grafts, orthograde flow in the vertebrobasilar system, and avoiding complex skull base manipulation. V3 bypass is characterized by profound and simultaneous vascular reconstruction of the posterior circulation, which is achieved by intracranial-intracranial or multiple bypasses in conjunction with skull base techniques. These posterior circulation vessels not only play a pivotal role in the bypass modalities designed for vertebrobasilar lesions but can also be implemented to revascularize the anterior circulation, thereby becoming a systematic methodology.